Improvement in use of best practice in the care of patients with oral mucositis in a comprehensive cancer center in Iran: a best practice implementation case study. Issue 1 (25th March 2022) - Alizadeh, Mahasti; Moradi, Siavash; Zaboli, Ehsan; Emadian, Seyedeh Fatemeh; Ghorbani, Anahita; Hedayatizadeh Omran, Akbar; Alizadeh Navaei, Reza
ABSTRACT: Introduction: Oral mucositis is a common debilitating complication of cancer treatments, particularly chemotherapy and radiation. Objectives: The purpose of this study was to improve oral mucositis prevention and control among cancer patients through the implementation of best practice guidelines in a tertiary referral center in Northern Iran. Methods: A clinical audit design was utilized in this implementation project. A preimplementation audit was conducted against nine best practice criteria for the prevention and treatment of oral mucositis among new cases of cancer patients in November and December 2019. Fifty cancer patients and 20 nurses participated in this phase of the clinical audit. The next step included a facilitated multidisciplinary focus group identifying targeted strategies and implementing them, completed in late December 2019. A postimplementation audit was then conducted on another 50 cancer patients and the same 20 nurses in January and early February 2020. The project utilized the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice software. Results: The preimplementation audit revealed gaps between the current practice and best practice across eight of the nine criteria. After implementing the targeted strategies, the outcomes improved across most of the criteria in the follow-up audit: 80% increase was observed in compliance of staff education, 100% increase in providing standard oral hygiene protocol in place, 64% increase in carrying out a dental examination and conducting initial oral cavity examination, and also 34% increase in conducting of ongoing oral cavity examination by a dentist, and finally 100% increase in providing preventive and therapeutic oral care regimens in place and oral pain assessment using a validated tool. Conclusion: The results of this project indicate that clinical auditing is an effective approach to the assessment of evidence-based care practices for oral mucositis among new cancer patients. Evidence-based oral mucositis management among cancer patients can be achieved by educating the patients and nursing staff using the newest guidelines and dentists' comprehensive dental and oral hygiene examinations.